Feed additives for swine: Fact sheets – high dietary levels of copper and zinc for young pigs, and phytase - Jacela, Jay Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Renter, David G.; Dritz, Steven S. (My University, 2012)
Copper and zinc play important roles in many physiological processes. Dietary copper levels of 5 to 10 ppm and zinc levels of 50 to 125 ppm are generally enough to meet the pig’s nutrient requirement for these processes. However, when supplied at high concentrations (100 to 250 ppm for copper and 2000 to 3000 ppm for zinc), these two minerals are known to exert positive influences on growth rate. In addition, copper is efficacious even when antibiotics also are included in the diets. This suggests that the response to copper is additive to the response to antimicrobials. Response to high levels of dietary copper decreases with increasing age and with longer periods of administration. Zinc fed at high dietary levels (2000 to 3000 ppm) reduces incidence of diarrhea and increases weight gain in newly weaned pigs. However, these high levels of dietary zinc are beneficial to pigs only during the early phases of the nursery period. Thus, feeding period for high dietary levels of zinc should be limited to approximately 3 weeks after weaning. Additive effects are usually not observed in weaned pigs when high levels of copper and zinc are added together. However, the data is conflicting and this observation needs to be further investigated.4,6-8 Recent research has indicated that feeding high levels of zinc until pigs reached 12 kg, then feeding high levels of copper for the remainder of the nursery period, was the most cost-effective strategy. Pigs need dietary phosphorus for normal body maintenance and growth. It is an essential element that is required in many physiological processes in the pig’s body and thus suffi cient amounts must be included in the diet. This element is abundant in most grains found in swine diets. However, only a small amount of phosphorus is utilized from grains, because the majority of the phosphorus exists in a form (phytate) that is not digestible in swine. The digestibility of phytate phosphorus can be increased when supplemental phytase is included in the diet.
Keywords: Swine; Feed additives; Copper; Zinc; Phytase